THE EFFECTS OF ANGLE OF ATTACK, REYNOLD NUMBERS AND WINGLET STRUCTURE ON THE PERFORMANCE OF CESSNA 172 SKYHAWK - Henny Pratiwi (Institut Teknologi Dirgantara Adisutjipto, 2018)
This research aims to investigate the effects of angle of attack, Reynold numbers and winglet structure on the performance of Cessna 172 Skyhawk aircraft with winglets variation design. Winglets improve efficiency by diffusing the shed wingtip vortex, which reducing the drag due to lift and improving the wing’s lift over drag ratio. In this research, the specimens are the duplicated of Cesnna 172 Skyhawk wing with 1:40 ratio made of balsa wood. There are three different winglet designs that are compared with the one without winglet. The experiments are conducted in an open wind tunnel to measure the lift and drag force with Reynold numbers of 25,000 and 33,000. It can be concluded that the wings with winglets have higher lift coefficient than wing without winglet for both Reynold numbers. It was also found that all wings with winglets have higher lift-to-drag ratio than wings without winglet where the blended 45o cant angle has the highest value.